Libraries + IRW = Big Read Success! - Coates, Jan (Maine Policy Review, 2013)
Jan Coates presents a case study of how Island Readers and Writers collaborated with local libraries in the Mt. Desert Island (Maine) area to encourage reading and community engagement through two "Big Read” events.